PENGARUH MODEL INQURY LEARNING TERHADAP HASIL BELAJAR SISWA TEMA KEPEMIMPINAN KELAS VI SD NEGERI 094142 DOLOK MARAWA - Olowardiman Saragih; Rumiris Lumban Gaol; Patri Janson Silaban; Antonius Remigius Abi; Irmina Pinem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Inqury Learning model on student learning outcomes in class VI Leadership Theme of SD Negeri 094142 Learning Year 2024/2025. The research method used is experimental method with quantitative research type. To obtain the data required a test instrument of 25 questions and a questionnaire of 25 questionnaire items. The number of research samples was 31 students based on purposive sampling technique. To find out the initial ability of students, the research conducted a Pretest with an average score of 53.29 which was in the poor category. The results of the Pretest have an increase from the results of the Posttest given previously with the average student score reaching 73.54 in the good category. It can be said that the success rate of student learning outcomes by using the Inqury Learning model increases and has an effect with a very strong category as evidenced by the results of the calculation of the correlation coefficient test obtained the results of r_hitung ≥ r_tabel with the results of 0.814 ≥ 0.355. Furthermore, hypothesis testing compares the value of t_count ≥ t_table. Obtained the value of t_count = 7.547 while t_table = 1.695. Because t_count ≥ t_table (7.547 ≥ 1.695) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Inqury Learning model (X) on student learning outcomes (Y).